(untitled) (Torani Journal of Fisheries and Marine Science, 2026)
The coastal region of East Sumba Regency possesses significant natural resources with high productivity, including both renewable and non-renewable resources. Renewable coastal ecosystems such as mangroves, coral reefs, seagrass beds, and fisheries play an important role in supporting local livelihoods while offering strong potential for marine ecotourism development. Several coastal areas, including Londa Lima Beach, Walakiri Beach, Tapil Beach, Puru Kambera Beach, and Wanga Beach, exhibit diverse physical and social characteristics that can support ecotourism activities. This study aims to assess the sustainability of coastal resource utilization in East Sumba Regency by evaluating the suitability of marine ecotourism development through the integration of ecological, economic, social, cultural, and institutional dimensions. A quantitative approach was employed using a scoring-based method derived from field surveys, data processing, and descriptive analysis. The analysis applies several physical parameters, including beach type, coastline length, seabed material, current velocity, hazardous biota, land cover, and freshwater availability. Social aspects are assessed using the 4A tourism framework: attraction, accessibility, amenities, and ancillary services. The results provide insights to support sustainable marine ecotourism development in East Sumba Regency. The result shows that The Tourism Suitability Index (TSI) for Tapil Beach is 1.15, Wanga Beach with a score of 1.41, Walakiri Beach is 2.09, Puru Kambera Beach with a score of 1.38, and Londa Lima Beach with a score of 2.0. Based on the TSI analysis, the Walakiri Beach and Londa Lima Beach are suitable locations for beach-based ecotourism development